Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/bioinformatics/btw101
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-CENTAURI: assessing novel centromeric repeat sequence variation with long read sequencing

Abstract: Motivation: Long arrays of near-identical tandem repeats are a common feature of centromeric and subtelomeric regions in complex genomes. These sequences present a source of repeat structure diversity that is commonly ignored by standard genomic tools. Unlike reads shorter than the underlying repeat structure that rely on indirect inference methods, e.g. assembly, long reads allow direct inference of satellite higher order repeat structure. To automate characterization of local centromeric tandem repeat sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 17 publications
1
53
0
Order By: Relevance
“…Large palindromes may thus transpose and seed 5S blocks to distal locations. Supporting this, a recent study of a human centromeric satellite (using long read PacBio sequencing) showed increased frequencies of inversions in acrocentric chromosomes compared to other chromosomes [71]. Perhaps, acrocentromeric positions of rDNA could be particularly vulnerable to such rearrangements and/or inversions.…”
Section: Discussionmentioning
confidence: 92%
“…Large palindromes may thus transpose and seed 5S blocks to distal locations. Supporting this, a recent study of a human centromeric satellite (using long read PacBio sequencing) showed increased frequencies of inversions in acrocentric chromosomes compared to other chromosomes [71]. Perhaps, acrocentromeric positions of rDNA could be particularly vulnerable to such rearrangements and/or inversions.…”
Section: Discussionmentioning
confidence: 92%
“…Figure 1 shows a dot-plot of the consensus HOR sequence on the X centromere (referred to as DXZ1) formed by 12-monomers with length 2,055. HORs typically occupy multi megabase-sized segments that include rearrangements and transposon insertions (Sevim et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have successfully mined sequence data to identify tandem repeats that have been developed into FISH probes (Novak et al, 2013;Sevim et al, 2016;Novák et al, 2017;Easterling et al, 2018;Mlinarec et al, 2019). Here we carried out a thorough analysis of PacBio Single Molecule, Real-Time (SMRT) reads (n=1,037,871 reads), each consisting of sequences greater than 5,000 bp long.…”
Section: Sequence Datamentioning
confidence: 99%